The Value of CEUS in Distinguishing Cancerous Lymph Nodes From the Primary Lymphoma of the Head and Neck - Nie, Ji; Ling, Wenwu; Yang, Qianru; Jin, Hongyu; Ou, Xuejin; Ma, Xuelei (Frontiers in Oncology, 2020)
Abstract Aim: The purpose of this study was to assess the ability of contrast-enhanced ultrasonography (CEUS) in the differential diagnosis of and cancerous lymph nodes. Material and methods: CEUS was performed in the cervical nodules of included patients, and the diagnoses were confirmed by pathological examination. CEUS images and parameters of head and neck lymphomas were compared with those of cancerous lymph nodes. Besides, receiver operating characteristic (ROC) curve was operated to access the diagnostic value of CEUS. Result: Finally, a total of 63 head and neck lymphomas and 80 cervical cancerous lymph nodes were enrolled in this study. Results showed that the CEUS images of lymphoma were mainly characterized by homogeneous enhancement (71.43%), and about half of them were centripetal perfusion (58.73%); while most CEUS images of cancerous lymph nodes were inhomogeneous enhancement (82.50%) and centripetal perfusion (92.50%). Quantitative analysis of CEUS parameters indicated that PI (derived peak intensity) and AUC (area under the curve) of lymphomas were both lower than those of cancerous lymph nodes (PI: 8.78 vs 10.51, AUC: 652.62 vs 784.09, respectively) (P<0.05). ROC analysis showed that the sensitivity of CEUS parameters in the differential diagnosis was significant (80.00%), although the specificity was not high (47.62%). When combined parameters with the image features, the accuracy of diagnosis was greatly improved (from 0.655 to 0.899). Conclusion: In conclusion, CEUS could be a promising tool for the differential diagnosis of head and neck lymphomas and cancerous lymph nodes.